In stone and story : early Christianity in the Roman world - Longenecker, Bruce W. (Grand Rapids, Michigan : Baker Academic, 2020)
This beautifully designed, full-color textbook introduces the Roman background of the New Testament by immersing students in the life and culture of the thriving first-century towns of Pompeii and Herculaneum, which act as showpieces of the world into which the early Christian movement was spreading. Bruce Longenecker, a leading scholar of the ancient world of the New Testament, discusses first-century artifacts in relation to the life stories of people from the Roman world. The book includes discussion questions, maps, and 175 color photographs.
Protocols of engagement -- Human meaning in stone and story -- Fire in the bones -- Accessing the first-century world : timeline of events -- Protocols of popular devotion -- Deities and temples -- Sacrifice and sin -- Peace and security -- Genius and emperor -- Mysteries and knowledge -- Death and life -- Protocols of social prominence -- Prominence and character -- Money and influence -- Literacies and status -- Combat and courts -- Business and success -- Protocols of household effectiveness -- Household and slaves -- Family and solidarity -- Piety and pragmatism -- Powers and protection -- Banqueting and the dead.
Includes bibliographical references (pages 268-282) and index.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Pompeii (Extinct city) -- Church history; Pompeii (Extinct city) -- Civilization; Herculaneum (Extinct city) -- Church history; Herculaneum (Extinct city) -- Civilization; Church history